2021
DOI: 10.1002/ieam.4430
|View full text |Cite
|
Sign up to set email alerts
|

National scale down‐the‐drain environmental risk assessment of oxybenzone in the United States

Abstract: This article is part of the special series "Consequences of Sunscreen Product Use on Aquatic Environments." This series documents the current state of knowledge concerning potential impacts of chemicals derived from sunscreen products on freshwater and marine ecosystems, including coral reefs. Specific topics discussed include use patterns, environmental loadings, potential exposures, toxicological effects, and future research needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…This compound is hard to remove from wastewaters and has been identified in tissues of many fish species across Europe (Schneider & Lim, 2019). In most cases, levels measured in surface water were two orders of magnitude below the predicted‐no‐effect concentrations (Burns et al, 2021). The second validated compound, metribuzin, is an herbicide which was detected below 1 µg/L each year between 2015 and 2017 in the Huron River (Giroux, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This compound is hard to remove from wastewaters and has been identified in tissues of many fish species across Europe (Schneider & Lim, 2019). In most cases, levels measured in surface water were two orders of magnitude below the predicted‐no‐effect concentrations (Burns et al, 2021). The second validated compound, metribuzin, is an herbicide which was detected below 1 µg/L each year between 2015 and 2017 in the Huron River (Giroux, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the United States Food and Drug Administration issued their intent to publish an Environmental Impact Statement for two important UV filters, oxybenzone (BP-3) and octinoxate (EHMC). A robust environmental risk assessment (ERA) for BP-3 in US freshwaters was recently published (Burns et al, 2021), and the present study presents a comparable assessment for the other UV filter of regulatory interest, EHMC.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review of EHMC freshwater monitoring data identified no studies conducted in the United States, similar to the review for BP-3 (Burns et al, 2021). Due to the lack of monitoring data specific to the United States, a robust exposure modeling approach is needed to predict concentrations from down-the-drain wash-off of EHMC that reflect the variability in population and geographical features across the region.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CPCP ingredients including microplastics (Burns & Boxall, 2018 ), parabens (Yamamoto et al, 2011 ), and most recently ultraviolet (UV) filters (Mitchelmore et al, 2021 ) are receiving attention. The CPCPs can enter the aquatic environment through their intended use and subsequent wash‐off, either directly (e.g., swimming) or indirectly through down‐the‐drain release to wastewater (Burns et al, 2021 ). Therefore, the CPCP industry is developing product stewardship programs to assess the environmental safety of ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…The CPCP industry aims to develop a systematic risk‐based prioritization approach that begins with lower tier screening‐level assessments, to identify which ingredients are the highest priority to assess using higher tier ERA methods. These assessments will focus on down‐the‐drain freshwater exposure scenarios on which most of the ecotoxicological hazard and exposure knowledge is based; however, in certain scenarios, for example, products used at the beach and coastal locations, the ERA exposure scenario may need to be extended to include direct wash‐off during recreation (Burns et al, 2021 ). In these special circumstances, it is particularly important to consider relevant marine toxicological data (e.g., cnidarians, mollusks, echinoderms; European Chemicals Agency [ECHA], 2008 ).…”
Section: Introductionmentioning
confidence: 99%